2019
DOI: 10.1080/20008198.2019.1644127
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods investigation of parent-child posttrauma discussion and the effects of encouraging engagement

Abstract: Recent developments in the child trauma field include preventative interventions that focus on augmenting parental support. However, we have limited knowledge of how parents experience trauma conversations with children. We examined how parents and children experienced both spontaneous trauma conversations and a structured task in which they generated a joint trauma narrative, following the child’s experience of an acute trauma. Parent and child ratings of distress during the structured narrative were low for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Research on children with medical conditions has demonstrated the importance and health-related gains of open parent–child communication about a medical condition (Middleton et al, 2018; O’Toole et al, 2021), more specifically when the child is overweight (see Gillison et al, 2016), in cases of trauma (McGuire et al, 2019), and in terminal cancer (see A. R. Rosenberg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on children with medical conditions has demonstrated the importance and health-related gains of open parent–child communication about a medical condition (Middleton et al, 2018; O’Toole et al, 2021), more specifically when the child is overweight (see Gillison et al, 2016), in cases of trauma (McGuire et al, 2019), and in terminal cancer (see A. R. Rosenberg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research on children with medical conditions has demonstrated the importance and health-related gains of open parent-child communication about a medical condition (Middleton et al, 2018;O'Toole et al, 2021), more specifically when the child is overweight (see Gillison et al, 2016), in cases of trauma (McGuire et al, 2019), and in terminal cancer (see A. R. Rosenberg et al, 2016). These studies provide growing evidence that sensitive, timely, and age-appropriate information is helpful and important for a child, even in cases of distressful disclosures (Aldridge et al, 2017).…”
Section: Talking About Appearance: a "Double-edged Sword"mentioning
confidence: 99%
“…We also did not specifically ask about prior history of PTSD. The sample was predominantly Caucasian and participating required a parent to be willing and able to spare their time to be involved in the project, which likely skewed our sample towards parents who are keen to engage with their child about the trauma (Alisic et al, 2017;McGuire et al, 2019). Findings cannot necessarily be generalised to intentional trauma exposures such as child maltreatment, or to children living in more complex family environments, where prior experiences of trauma in the parent or the child may be important.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Some evidence suggests that both too little and too much conversation about a traumatic event (and, as we have discussed, conversation that focuses on youth vulnerability) can each heighten children’s distress. Creating a climate for a child or young person to talk if they choose to do so is important, yet waiting until the child raises their concerns may preclude potentially helpful interactions with their parent ( McGuire, Hiller, Cobham, Haag, & Halligan, 2019 ).…”
Section: What Can Buffer the Effects Of The Pandemic On Children?mentioning
confidence: 99%